Whole Genome Wide Expression Profiles on Germination of Verticillium dahliae Microsclerotia - Hu, Dongfang (Public Library of Science, 2014)
Verticillium dahliae is a fungal pathogen causing Verticillium wilt on a range of economically important crops. Microsclerotia are its main survival and dormancy structures and serve as the primary inoculum on many hosts. Studies were conducted to determine the effect of temperature (5 to 50°C), pH (2 to 12) and nutrient regimes on microsclerotia germination. The optimal condition for microsclerotium germination was 20°C with pH 8.0 whereas nutrient regimes had no significant effect on its germination. The whole genome wide expression profiles during microsclerotium germination were characterized using the Illumina sequencing technology. Approximately 7.4 million of 21-nt cDNA tags were sequenced in the cDNA libraries derived from germinated and non-germinated microsclerotia. About 3.9% and 2.3% of the unique tags were up-regulated and down-regulated at least five-fold, respectively, in the germinated microsclerotia compared with the non-germinated microsclerotia. A total of 1654 genes showing differential expression were identified. Genes that are likely to have played important roles in microsclerotium germination include those encoding G-protein coupled receptor, lipase/esterase, cyclopentanone 1,2-monooxygenase, H(+)/hexose cotransporter 1, fungal Zn(2)-Cys(6) binuclear cluster domain, thymus-specific serine protease, glucan 1,3-beta-glucosidase, and alcohol dehydrogenase. These genes were mainly up-regulated or down-regulated only in germinated microsclerotia, compared with non-germinated microsclerotia. The differential expression of genes was confirmed by qRT-PCR analysis of 20 randomly selected genes from the 40 most differentially expressed genes.